The efficiency of 20 years of Indonesian zakat institution: Data Envelopment Analysis (DEA) approach - Aftuqa Sholikatur Rohmania; Erlinda Sholihah (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This study aims to analyze the efficiency of BAZNAS performance for 20 years, during 2002-2021.Methodology – This research uses a quantitative approach with the Data Envelopment Analysis (DEA) method. The secondary data source is an annual report from the official National Amil Zakat Agency (Badan Amil Zakat Nasional, BAZNAS) website from 2002-2021. The analysis technique is assisted by maxDEA software.Findings – The results showed BAZNAS gained an average efficiency of over the period 2002 - 2021 worth 90.86%, meaning that over the 20 years, BAZNAS operated showed a level of inefficiency. Further analysis, during 2018-2021, BAZNAS has shown its productivity in improving performance efficiency by achieving an optimal efficiency level worth 100%. That implies BAZNAS needs to improve its management performance by considering the suitability of inputs and outputs.Implications – This research contributes to improving knowledge about BAZNAS performance efficiency. This research also provides insights for policymakers as an evaluation and decision-making in improving the performance of zakat institutions, especially BAZNAS.Originality – This research saw the efficiency of BAZNAS’ performance for 20 years or from its operation until now. It can show the level of public trust in BAZNAS in the management of zakat, infaq, and sadaqah (ZIS) in Indonesia.